Is it wrong to try to pick up girls in a dungeon? On the side. Sword oratoria. 12 - Omori, Fujino; Yagi, Takashi (Yen Press, 2020)
"The Dungeon's Under Resort is supposed to be safe, yet when Lefiya ends up lost in its forest with Bell Cranell, it's just her luck that peril would emerge from the foliage. The dangers plaguing Loki Familia have followed them even here, and it's up to Lefiya to make sure they both make it out alive! Despite her familia's exhaustion, Loki has plans for the immediately upon their return and sets to work preparing yet another excursion. This trip may look like a beach vacation, but even in paradise, monsters lurk beneath the waves."--Page [4] of cover.